1997
DOI: 10.1074/jbc.272.10.6653
|View full text |Cite
|
Sign up to set email alerts
|

The Mitogenic and Myogenic Actions of Insulin-like Growth Factors Utilize Distinct Signaling Pathways

Abstract: It is well established that mitogens inhibit differentiation of skeletal muscle cells, but the insulin-like growth factors (IGFs), acting through a single receptor, stimulate both proliferation and differentiation of myoblasts. Although the IGF-I mitogenic signaling pathway has been extensively studied in other cell types, little is known about the signaling pathway leading to differentiation in skeletal muscle. By using specific inhibitors of the IGF signal transduction pathway, we have begun to define the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
548
6
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 590 publications
(586 citation statements)
references
References 63 publications
29
548
6
1
Order By: Relevance
“…To further con®rm that activation of the c-Raf kinase pathway was involved in the cellular response to IGF-I, we used the inhibitors PD098059 and geldanamycin. PD098059 blocks the c-Raf activation of MAP kinase (Coolican et al, 1997), and geldanamycin selectively promotes c-Raf protein degradation (Schulte et al, 1996). Both PD098059 (2 mM) and geldanamycin (0.5 mM) blocked IGF-I e ects on MAP kinase activation ( Figure 1c) and cell proliferation (not shown).…”
Section: C-raf Kinase Pattern Of Expression and Modulation Of Activitymentioning
confidence: 89%
See 1 more Smart Citation
“…To further con®rm that activation of the c-Raf kinase pathway was involved in the cellular response to IGF-I, we used the inhibitors PD098059 and geldanamycin. PD098059 blocks the c-Raf activation of MAP kinase (Coolican et al, 1997), and geldanamycin selectively promotes c-Raf protein degradation (Schulte et al, 1996). Both PD098059 (2 mM) and geldanamycin (0.5 mM) blocked IGF-I e ects on MAP kinase activation ( Figure 1c) and cell proliferation (not shown).…”
Section: C-raf Kinase Pattern Of Expression and Modulation Of Activitymentioning
confidence: 89%
“…Levels of phosphorylated MAP kinase were measured and normalized with respect to total MAP kinase levels under each condition. PD098059 (2'-amino-3'-methoxyavone), a selective inhibitor of MAP kinase kinase (Coolican et al, 1997), was purchased from Calbiochem (San Diego, CA, USA). Geldanamycin treatment selectively depletes c-Raf cellular contents, disrupting the c-Raf/MAP kinase signalling pathway (Schulte et al, 1996).…”
Section: Immunoblotting and Map Kinase Assaymentioning
confidence: 99%
“…39 Since signaling through the PI3-kinase pathway has been shown to be critical for normal skeletal myoblast survival/differentiation, 20,21,23,24 and Ras signaling abrogates differentiation, 29,30,37,38 we focused our attention on the Raf/MEK pathway which has been shown to be anti-apoptotic. 33 We have shown that signaling through MEK may play a role in the survival of myoblasts in GM since the abrogation of MEK signaling increases apoptosis in GM to almost the level observed when myoblasts are cultured in DM.…”
Section: Discussionmentioning
confidence: 99%
“…Myoblasts expressing constitutively active Ras (A2:H-Ras myoblasts) are differentiation-defective 29,30 ( Figure 4A) and apoptose at a level less than 1/10 that of the parental 23A2 myoblasts in either GM ( Figure 4B Signaling by Ras through either the PI3-kinase/Akt pathway 32 or the Raf/MEK/MAPK pathway has been implicated in cell survival. 33 Since PI3 kinase/Akt signaling has been implicated in the normal survival/differentiation of skeletal myoblasts, 20,21,23,24 we focused on the role of Raf/ MEK signaling in the increased survival of A2:H-Ras myoblasts. We have previously reported that PD 098059, a selective MEK inhibitor, does not affect the differentiation of skeletal myoblasts.…”
Section: Abrogation Of Differentiation Can Be Separated From Abrogatimentioning
confidence: 99%
“…6 Many intracellular proteins are involved in transduction of IGF signals from the membrane to the nucleus. 7 Some proteins are specific to this pathway, while others represent ubiquitous components of several transduction cascades. The activity of IGF axis is finely regulated not only by the availability of IGF factors and density of the IGF1R on the cell surface but also by a family of six proteins, the IGF binding proteins (IGFBPs), which bind IGF with high affinity.…”
Section: Introductionmentioning
confidence: 99%